2021
DOI: 10.3390/qubs5020015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Beam Conditions in Ground Irradiation Tests on Degradation of Photovoltaic Characteristics of Space Solar Cells

Abstract: We investigated the effects of irradiation beam conditions on the performance degradation of silicon and triple-junction solar cells for use in space. The fluence rates of electron and proton beams were varied. Degradation did not depend on the fluence rate of protons for both cells. A higher fluence rate of electrons caused greater degradation of the Si cell, but the dependence was due to the temperature increase during irradiation. Two beam-area expansion methods, defocusing and scanning, were examined for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…They have found that the photovoltaic properties of both the solar cells are degraded irrespective of the fluence rate or the irradiation mode. The details are discussed in [25].…”
Section: Research Results Using the Ion-implantermentioning
confidence: 99%
See 1 more Smart Citation
“…They have found that the photovoltaic properties of both the solar cells are degraded irrespective of the fluence rate or the irradiation mode. The details are discussed in [25].…”
Section: Research Results Using the Ion-implantermentioning
confidence: 99%
“…Using these accelerators, we have been involved in research on the destruction of tumor cells in human bodies (proton beam radiotherapy) [3,4], the transmutation of DNAs in plants and bacteria (ion beam breeding) [5][6][7], ion beam material modification [8][9][10] and ion beam analysis for materials [11][12][13]. The accelerators at WERC have also been utilized to simulate the radiation effects on materials which are related to nuclear power plants [14][15][16] and those of space electronics [17][18][19][20][21][22][23][24][25]. Electronic systems are severely affected by the radiation environment in space.…”
Section: Introductionmentioning
confidence: 99%
“…Note that in the cases of proton and He + -ion irradiations, it is confirmed that the sample temperature does not change, while a water-cooled sample plate was used in the case of the electron irradiation. 18) Thus, the sample temperature was kept at room temperature (ambient) during all the irradiations.…”
Section: Methodsmentioning
confidence: 99%